2013
DOI: 10.3389/fgene.2013.00273
|View full text |Cite
|
Sign up to set email alerts
|

Copy-number changes in evolution: rates, fitness effects and adaptive significance

Abstract: Gene copy-number differences due to gene duplications and deletions are rampant in natural populations and play a crucial role in the evolution of genome complexity. Per-locus analyses of gene duplication rates in the pre-genomic era revealed that gene duplication rates are much higher than the per nucleotide substitution rate. Analyses of gene duplication and deletion rates in mutation accumulation lines of model organisms have revealed that these high rates of copy-number mutations occur at a genome-wide sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
141
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(146 citation statements)
references
References 140 publications
(224 reference statements)
5
141
0
Order By: Relevance
“…Structural variations are known to accumulate during the inbreeding process (Katju and Bergthorsson 2014); however, the extent to which these variations contribute to divergence in natural mouse populations remained unknown until now. We found that CNVs show stronger population stratification in wild mice than in humans (Jakobsson et al 2008;Itsara et al 2009) and contribute substantially to genetic differences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Structural variations are known to accumulate during the inbreeding process (Katju and Bergthorsson 2014); however, the extent to which these variations contribute to divergence in natural mouse populations remained unknown until now. We found that CNVs show stronger population stratification in wild mice than in humans (Jakobsson et al 2008;Itsara et al 2009) and contribute substantially to genetic differences.…”
Section: Discussionmentioning
confidence: 99%
“…The amplification of whole genes can have a direct impact on gene expression by changing gene dosage (Perry et al 2007;Watkins-Chow and Pavan 2008;Henrichsen et al 2009b;Orozco et al 2009;Stingele et al 2012;Katju and Bergthorsson 2014). If a copy number change is beneficial, it will be favored by selection and retained more frequently in a population, resulting in average differences in gene copy number between populations.…”
Section: Amplifications Versus Deletionsmentioning
confidence: 99%
“…Indeed, recombination events are probably countering such association, especially as the VGSC gene and amplified detoxification genes are located on distant genomic regions. In addition, fitness costs associated with both kdr mutations and gene amplifications have been identified (Kondrashov 2012;Brito et al 2013;Katju and Bergthorsson 2013;Rinkevich et al 2013 …”
Section: Gene Amplifications Associated With Pyrethroid Resistancementioning
confidence: 99%
“…Most nonsynonymous variants impacting CCEs were identified in Thailand with CCEAE4A and CCEAE3A impacted by multiple variants strongly associated with deltamethrin resistance. Elevated copy numbers of these genes were also identified in Thailand, suggesting that their amplification may have been followed by their neofunctionalization under insecticide selection pressure (Katju and Bergthorsson 2013). Interestingly, the best orthologous gene of CCEAE4A in the sheep blowfly, Lucilia cuprina (LcαE7), encodes an esterase associated with organophosphate resistance through a single point mutation enhancing its activity toward these chemicals (Newcomb et al 1997).…”
Section: Polymorphisms Associated With Pyrethroid Resistancementioning
confidence: 99%
“…For example, duplications or mutations in globulin reflect the metabolic demands and environmental oxygen availability during the different embryonic or post-birth life stages of an individual, or during the infection of erythrocytes by the malarial parasite (Lam and Jeffreys, 2006;Opazo et al, 2013); duplications in the AQP7 gene, which codes for a family of water-selective membrane channels, is representative of the adaptations in thermoregulation and energy utilization through biological transmembrane transport (Dumas et al, 2007). Previous research has also suggested that mutations and duplications in the genes could also lead to the development of proteins that are harmful to the species; therefore, there is a high possibility that approximately 90% of the new copied genes is pseudogenized at the epigenetic level, affecting its functionality (Rodin and Riggs, 2003;Katju and Bergthorsson, 2013). Therefore, the fate of the vast majority of gene duplications is detrimental, leading to its inhibition or removal by natural selection.…”
Section: Introductionmentioning
confidence: 99%